Assessment of radiological parameters of river water and sediment in some oil producing communities of delta state of Nigeria. Issue 3 (3rd July 2019) - Iwetan, C. N.; Fuwape, I. A.; Aiyesanmi, A. F.; Ayorinde, T. T.
Abstract: Gamma ray spectra of natural radioactivity from 238 U, 232 Th, and 40 K in sediments and water samples from rivers in eleven oil-producing and two non-oil producing communities in Delta state of Nigeria have been evaluated using gamma-ray spectrometer with the hyper-pure germanium detector. Measured activity concentrations in water samples ranged from 1.17 Bq L −1 to 14.65 Bq L −1 for 40 K; 0.26 Bq L −1 to 3.11 Bq L −1 for 232 Th and 1.05 Bq L −1 to 5.58 Bq L −1 for 238 U. The specific activity due to 232 Th is found to be relatively low compared to that of 238 U in all the water sample investigated. In the sediment samples, activities of 40 K ranged from 32.47 Bq kg −1 to 525.1 Bq kg −1, 232 Th ranged from 6.31 Bq kg −1 to 19.33 Bq kg −1 and values of 238 U ranged from 4.45 Bq kg −1 to 18.69 Bq kg −1 . The radiological hazard indices reported in this work include absorbed dose (D), radium equivalent dose (Req), external and internal hazard indices (Hex, Hin), annual effective dose equivalent (AEDE), lifetime average annual dose associated with water resources (LAAD), and excess lifetime cancer risk (ELCR). The values of the radiological hazard indices obtained were observed to be lower than limits internationally reported for both water and sediment, but observed concentration values at the oil-producing study areas are in most cases higher than values from the non-oil producing sites.